Cistus incanus and Pelargonium sidoides extracts block enveloped viruses inluding HIV, Ebola and Marburg from entering human cells - Cock, I.E. (Pharmacognosy Communications)
Recent studies have reported that extracts prepared from the medicinal plants Cistus incanus and Pelargonium sidoides prevent HIV from binding to human cells, thereby preventing it from those infecting cells.1,2 The extracts were reported to inhibit a wide range of HIV-1 and HIV-2 clinical isolates, including a viral isolate which is resistant to all other drugs which are generally used as a part of normal anti-retroviral combinational therapies. The phytochemical extract compounds were found to target and bind to viral envelope proteins. The active compounds bind the cellular proteins and prevent them from interacting with host cell surface CD4 receptors. Of further interest, the research team also reported that the extracts not only blocked HIV cell entry, but had similar effects against both Ebola and Marburg viruses. The team speculated that the extracts may also have similar preventative effects against a wider range of enveloped viruses, included influenza viruses and therefore have broad medical implications. Notably, the study also trialled the extracts in long term studies to determine whether prolonged treatment would result in the development of viral resistance and reported no resistant viruses were found. The research has exciting implications. As the extracts have very different antiviral activities to all cur- rent clinical therapies, the extracts may be useful complementary therapies for the prevention and treatment of a wide range of viral diseases.